Soil health and microbial network analysis in a wheat-maize cropping system under different wheat yields - Xinzhan SUN; Tengteng LI; Jiangzhou ZHANG (Frontiers of Agricultural Science and Engineering)
Healthy soil is crucial for sustainable agriculture with soil microbiomes being key to soil health. However, comprehensive assessments of soil health and microbial community structures under different wheat yields have not been made. Therefore, soil samples were collected from wheat fields with differing yields at depths of 0–15 and 15–30 cm. The yields were categorized as low (Y1, 3.75 t·ha−1), medium (Y2, 6.00 t·ha−1), high (Y3, 8.25 t·ha−1), and maximum (Y4, 10.1 t·ha−1), and soil health and microbial communities determined. The results showed that both yield category and soil depth significantly influenced SOC, TN, mineral nitrogen, AP and AK, enzyme activity, and soil bacterial communities. The soil health index in Y4 (0.51–0.87) was significantly higher than in Y3 (0.39–0.63), Y2 (0.27–0.45), and Y1 (0.21–0.52) at both 0–15 and 15–30 cm (expect Y1). Significant correlation was only found between soil health index at 0–15 cm and wheat yield, not at 15–30 cm. The bacterial and fungal network structure in Y4 was more complex and densely connected. Actinobacteria, Thaumarchaeota, and Ascomycota were identified as key drivers of soil health. Based on these results, the regulation of microbes has the potential to improve soil health and crop yields.